The Erotion of Regional Language Among Young Generation: An Ethnographic Study of Public Relations in Jakarta Society - Palandi, Thomas Adrian (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
The fading of local languages among young people is inseparable from the role of public relations, especially agencies under the auspices of the ministry of education and culture, language agencies that echo the national language and regional languages as national identity. The phenomenon of bilingualism is rife among young people in the Jakarta area, which can be called a threat to the loss of the national language. In an ethnographic review, public relations is how behaviour communicates to form relationships which emphasizes cultural activities that explore patterns of relationships built on public support. Through the cultural revitalization program campaigned by the public relations of the language agency, it is hoped that the use of regional languages or Indonesian can be proudly used by young people without considering regional languages to be ancient languages but still learning foreign languages languages as international languages.